EFFECT OF ACETIC ACID AND CLOFIBRATE ON PLASMA LIPID IN RATS WITH ATHEROSCLEROSIS - Khalid Sharaf (College of Education for Pure Sciences, 2005)
In this study two major groups of albino adult male rats (3-4 months old and 155-262g weight) were used as experimental model for this study. First group contains five healthy rats used as healthy control group. Second group consisted of twenty rats with atherosclerosis induced by hydrogen peroxide and cholesterol, which was further subdivided into four subgroups with five rats in each. First subgroup was orally treated with sunflower oil alone and considered atherosclerosis control group, the second subgroup was treated with 300mg clofibrate drug/kg rat body weight and considered hypolipidemic standard reference group, third and fourth subgroups were orally treated with 5.23 and 10.45mg acetic acid/kg body weight, respectively. Blood samples were collected from retro-ocular eye vein by using heparinized capillary tubes. Plasma total lipid (TL), total cholesterol (TC), high density lipoprotein-cholesterol (HDL-c) and liver total cholesterol (TC) were determined. Nutritional status of the rats was estimated throughout body weight gain and apparent digestibility. Analysis of variance and Duncan test showed that, the acetic acid caused an increase in plasma TL, TC, very low density lipoprotein-cholesterol and low density lipoprotein-cholesterol (VLDL-c+LDL-c), atherogenic indices, and liver TC values and a decrease in plasma HDL-c. Furthermore, body weight losses and bad nutritional status were recorded. Therefore, acetic acid was regarded as a hyperlipidemic material.